Air Emissions Characteristics of Coal-Fired Power Unit for Flexibility Generation - Yuliang DONG; Jiahai YUAN; Lirong MA (发电技术)
With the increasing share of renewable energy in power system, more and more coal-fired power units participate flexibility generation. For clarifying the air emission characteristics of flexibility generation, the operation history data of two subcritical coal-fired power units (600 MW and 300 MW) are used for regression analysis. In normal cyclic operation, power ramping-down will lead to a little increase in coal consumption rate and CO2 emissions factor. Meanwhile, the NOx emissions factor will decrease firstly and then increase when ramping down and the amplitude of variation is little in clean flue gas. The SO2 emissions factor will decrease a little while dust factor will increase a little when ramping down. In deep cycling operation, the increase in coal consumption rate and CO2 emissions factor will be much larger, while the NOx and dust emissions factors will increase substantially when SO2 emissions factor continues to decrease in clean flue gas. In start-up process, the NOx and dust emissions are much larger while SO2 emissions are slightly smaller than regular operating conditions. In addition, larger ramping rate has remarkable impact on NOx and SO2 in untreated flue gas and on dust in clean flue gas in deep cycling conditions.